Effect of different heating temperatures on foaming properties of camel milk proteins: A comparison with bovine milk proteins. (May 2020) - Lajnaf, Roua; Zouari, Ahmed; Trigui, Ines; Attia, Hamadi; Ayadi, M.A.
Abstract: The effect of different heat-treatment temperatures (70, 80, 90 and 100 °C) on the foaming properties (foam capacity and stability) and the physicochemical characteristics (surface hydrophobicity, ζ-potential, and interfacial tension values) of camel milk proteins was investigated. Overall, the results showed that while increasing the temperature, greater foamability was measured for camel milk proteins (up to 165%). This behaviour was linked to the heat denaturation and aggregation of camel milk proteins, which led to an increase in the surface hydrophobicity and a decrease in the electronegative charge and interfacial tension. Likewise, our results indicated that the highest β-casein amount in camel milk (∼44% of total proteins) as well as its secondary structure (β-sheet conformation) and its high hydrophobicity, regulated the foaming mechanism of camel milk proteins.